Globalization,the Output-Inflation Tradeoff, and Inflation - Harald Badinger (FIW - Research Centre International Economics, 2008)
This paper provides a comprehensive assessment of the relation between inflation and globalization, measured in terms of trade and financial openness. Using a large crosssection of 91 countries covering the period 1985-2004, we establish two main empirical regularities. Both higher trade and financial openness i) reduce central bank?s inflation bias,yielding lower average inflation, and ii) are associated with a larger output-inflation tradeoff. This evidence is at odds with the standard Barro-Gordon framework, which would require globalization to have a negative effect on the output-inflation tradeoff to yield lower equilibrium inflation, but it is consistent with a recent strand of new Keynesian models emphasizing the role of imperfect competition and wage rigidities. Moreover, our findings do not hold up for the OECD subsample, which suggests that a group of highly developed countries has been successful in creating an institutional framework for central banks that eliminates distortions due to the time inconsistency problem.
Keywords: E58; F41; F10; F30; 330; Globalization; Trade; Financial Openness; Inflation; Output Inflation Tradeoff